Faktor-Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil - Eka Ratnasari; Ainaya Rizki Nur Amalia; Nurhasanah; Erni Ratna Suminar (WOMB Midwifery Journal, 2025)
In 2020, the incidence of bleeding in Indonesia was 28.7%, caused by anemia in pregnant women. Anemia can increasei thei risk of preterm labor, low birth weight, and even maternal and infant mortality. Anemia is influenced by various factors, including maternal age, gestational agei, parity, education level, occupation, knowledge, and nutritional status. This study aims to determinei factors associated with anemia among pregnant women at thei Kalijaga Community Health Center in Cirebon City in 2025. This study uses an observational analytical design with cross-sectional design. There are maternal age, gestational age, parity, education, employment, nutritional status, knowledge of anemia incidence in pregnant women at Puiskeismas Kalijaga, Cirebon City in 2025. It is hoped that health workers, cadres or families will help increase the interest of pregnant women so that they want to participate in counseling activities both in pregnant women's classes, community health centers or integrated health posts (Posyandu) to provide health education in an effort to prevent anemia and improve maternal and infant health.